HUBUNGAN ANTARA KANDUNGAN PATI RESISTEN DAN KUALITAS TANAK BERAS SIGER (TIWUL MODIFIKASI) - Beni Hidayat; M. Muslihudin; Syamsul Akmal (Politeknik Negeri Lampung., 2018)
Resistant starch is a starch fraction that can not be hydrolyzed by digestive enzymes in the small intestine and classified as a prebiotic compound. Increasing the content of resistant starch to a certain amount in Siger Rice (modified tiwul) will decrease the cooking quality. The objective of this research was to study the relationship between resistant starch content and cooking quality of Siger Rice (eating quality, texture, and taste). The increase of resistant starch content in siger rice was done by the application of autoclaving-cooling cycling treatment, through steam stages, cooling to room temperature, followed by cooling at 4Â°C for 0 hours/control, 12 hours, 24 hours, 36 hours and 48 hours. The results showed that the increase of resistant starch content â‰¤ 10% (9.85%) will improve the quality characteristics of Siger Rice for all organoleptic scores, i.e., eating quality (7,15 to 8,2), texture (7.05 to 8.35), and flavor (6.95 to 8.15); on the contrary, the increase of resistant starch content more than 10% (14.25%) will decrease the cooking quality characteristics of Siger Rice for all organoleptic scores, i.e., eating quality (7.15 to 6.8), texture (7.05 to 6.6), and taste (6.95 to 6.4).